Halide solid state electrolyte, method of making and solid state battery
Patent Information
- Application Number
- CN202611501966.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]但现有卤化物固态电解质存在致命缺陷:材料表面配位不饱和位点多、化学活性极高,对空气、水氧极度敏感
[0050]本申请提供一种卤化物固态电解质及其制备方法和固态电池,通过在以Li3MCl6为基体的卤化物固态电解质表面依次设置包括快离子导体材料的第一包覆层、包括锂掺杂复合氧化物、含锂磷酸盐和含锂硅酸盐中至少一种的第二包覆层以及包括金属氧化物或所述类金属氧化物的第三包覆层,能够在基体外部形成兼顾锂离子传输、界面缓冲与外层防水氧侵蚀的梯度包覆结构,进而降低环境暴露引发的表面副反应和界面阻抗增长,提升卤化物固态电解质的空气稳定性及在固态电池中的应用可靠性。
Smart Images

Figure CN123018116A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a halide solid electrolyte, its preparation method, and a solid battery. Background Technology
[0002] High-energy-density all-solid-state lithium batteries are the core development direction for next-generation energy storage and power batteries. Halide solid electrolytes (Li-M-Cl) have outstanding advantages such as high room-temperature ionic conductivity, wide electrochemical window, and good interfacial compatibility with high-voltage ternary cathodes. They overcome the defects of easy oxidation of sulfide electrolytes and high interfacial impedance of oxide electrolytes, making them one of the best electrolyte systems suitable for high-nickel ternary cathodes.
[0003] However, existing halide solid electrolytes have a fatal flaw: they have numerous unsaturated coordination sites on their surface, exhibit extremely high chemical activity, and are highly sensitive to air, water, and oxygen. In normal environments, halide electrolytes undergo rapid hydrolysis side reactions, specifically manifested as: surface Cl... - It reacts with H2O in the air to produce corrosive HCl gas, and at the same time generates lithium salt insulating impurities, causing the electrolyte surface structure to become loose and collapse. Long-term exposure to air will also react with CO2 to produce a lithium carbonate passivation layer, which greatly hinders lithium ion transport and causes the electrolyte conductivity to decrease sharply.
[0004] Therefore, improving the stability of halide solid electrolytes in air, water, and oxygen is a technical problem that urgently needs to be solved. Summary of the Invention
[0005] This application provides a halide solid electrolyte, its preparation method, and a solid battery. The halide solid electrolyte of this application has good stability in air, water, and oxygen, and also has good ionic conductivity.
[0006] In a first aspect, this application provides a halide solid electrolyte, including a substrate and a coating layer, wherein the coating layer includes a first coating layer, a second coating layer and a third coating layer; the first coating layer covers at least a portion of the surface of the substrate, the second coating layer covers at least a portion of the surface of the first coating layer, and the third coating layer covers at least a portion of the surface of the second coating layer;
[0007] The chemical formula of the matrix includes Li3MCl6, wherein M includes at least one of Y, Sc, In, Ga and La;
[0008] The first coating layer comprises a fast ion conductor material;
[0009] The second coating layer includes at least one of lithium aluminate, lithium silicate, and lithium phosphate;
[0010] The third coating layer includes a metal oxide or a metal-like oxide.
[0011] In one specific embodiment, the fast ion conductor material includes LiNbO3, LiTaO3, Li4SiO4, Li3PS4, and Li7P3S. 11 At least one of Li3PO4.
[0012] In one specific embodiment, the lithium aluminate includes at least one of LiAlO2 and LiAl5O8;
[0013] And / or, lithium silicates include at least one of Li2SiO3 and Li2Si2O5;
[0014] And / or, lithium phosphate includes at least one of LiZr2(PO4)3, LiTi2(PO4)3 and LiHf2(PO4)3.
[0015] In one specific embodiment, the metal oxide includes at least one selected from Al2O3, TiO2, ZrO2, and HfO2;
[0016] And / or, the metal-like oxide includes SiO2.
[0017] In one specific embodiment, the thickness of the coating layer is less than or equal to 200 nm.
[0018] In one specific embodiment, the coating layer accounts for 2-12% of the mass of the halide solid electrolyte.
[0019] In one specific embodiment, the thickness of the first coating layer is 10-60 nm;
[0020] And / or; the thickness of the second coating layer is 10-50 nm;
[0021] And / or; the thickness of the third coating layer is 10-100 nm.
[0022] In one specific embodiment, the room temperature ionic conductivity retention rate of the halide solid electrolyte is greater than or equal to 93% after being exposed to ambient air at a dew point of -45°C for 4 hours.
[0023] In one specific embodiment, the method for preparing the halide solid electrolyte includes:
[0024] S1: Under an inert protective atmosphere, the matrix is dispersed in a first coating liquid, and a first stirring reaction is carried out at 40-65°C, followed by drying and a first annealing to obtain a first intermediate; wherein the first coating liquid includes the fast ion conductor material;
[0025] S2: Under an inert protective atmosphere, the first intermediate is dispersed in the second coating solution, and a second stirring reaction is carried out at 40-65°C, followed by drying and a second annealing to obtain the second intermediate; wherein the second coating solution includes at least one of lithium aluminate, lithium silicate and lithium phosphate;
[0026] S3: Under an inert protective atmosphere, the second intermediate is dispersed in the third coating solution, and a third stirring reaction is carried out at 40-65°C. After drying and third annealing, the halide solid electrolyte is obtained. The third coating solution includes a metal oxide or the metal-like oxide. The mass percentage of water in the first, second, and third coating solutions is independently less than 10 ppm.
[0027] The temperature of the first annealing is greater than the temperature of the second annealing, and the temperature of the second annealing is greater than the temperature of the third annealing.
[0028] Secondly, this application provides a method for preparing the above-mentioned halide solid electrolyte, comprising:
[0029] S1: The matrix is dispersed in a first coating solution, subjected to a first stirring reaction at 40-65°C, dried, and annealed to obtain a first intermediate; wherein the first coating solution includes the fast ion conductor material;
[0030] S2: The first intermediate is dispersed in the second coating solution, and a second stirring reaction is carried out at 40-65°C. After drying and second annealing, the second intermediate is obtained. The second coating solution includes at least one of lithium aluminate, lithium silicate and lithium phosphate.
[0031] S3: The second intermediate is dispersed in the third coating solution, and a third stirring reaction is carried out at 40-65°C. After drying and third annealing, the halide solid electrolyte is obtained; wherein the third coating solution includes a metal oxide or the metal-like oxide.
[0032] The temperature of the first annealing is greater than the temperature of the second annealing, and the temperature of the second annealing is greater than the temperature of the third annealing.
[0033] In one specific embodiment, in S1, the temperature is increased to 100-400°C at a heating rate of 1-5°C / min to perform the first annealing for 1-5 hours;
[0034] And / or, in S2, the temperature is increased to 100-400°C at a heating rate of 1-5°C / min for the second annealing for 1-5 hours;
[0035] And / or, in S3, the temperature is increased to 100-400℃ at a heating rate of 1-5℃ / min to carry out the third annealing for 1-5 hours;
[0036] And / or, the difference between the temperature of the first annealing and the temperature of the third annealing is less than or equal to 60°C.
[0037] In one specific embodiment, the first stirring reaction takes 2-5 hours;
[0038] And / or, the second stirring reaction time is 2-5 hours;
[0039] And / or, the third stirring reaction time is 2-5 hours.
[0040] In one specific embodiment, the first coating liquid further includes a dispersant and an organic solvent;
[0041] And / or, the second coating liquid further includes a dispersant and an organic solvent;
[0042] And / or, the third coating liquid also includes a dispersant and an organic solvent.
[0043] In one specific embodiment, the stirring speed of the first stirring reaction is 300-650 r / min;
[0044] And / or, the stirring speed of the second stirring reaction is 300-650 r / min;
[0045] And / or, the stirring speed of the third stirring reaction is 300-650 r / min;
[0046] And / or, the vacuum degree of the drying process is less than or equal to -0.08 MPa.
[0047] Thirdly, this application provides a solid-state battery, which includes the above-mentioned halide solid electrolyte.
[0048] In one specific embodiment, the solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the solid electrolyte layer includes the halide solid electrolyte.
[0049] In one specific embodiment, the solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode includes the halide solid electrolyte.
[0050] This application provides a halide solid electrolyte, its preparation method, and a solid-state battery. By sequentially depositing a first coating layer comprising a fast ion conductor material, a second coating layer comprising at least one of lithium-doped composite oxide, lithium phosphate, and lithium silicate, and a third coating layer comprising a metal oxide or the aforementioned metal-like oxide on the surface of a halide solid electrolyte based on Li3MCl6, a gradient coating structure that balances lithium-ion transport, interface buffering, and external waterproofing against oxygen erosion can be formed outside the substrate. This reduces surface side reactions and interface impedance growth caused by environmental exposure, and improves the air stability of the halide solid electrolyte and its reliability in solid-state batteries. Attached Figure Description
[0051] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0052] Figure 1 This is a schematic diagram of the structure of the halide solid electrolyte in some embodiments of this application.
[0053] Explanation of reference numerals in the attached figures:
[0054] 1: Matrix;
[0055] 2: First coating layer;
[0056] 3: Second coating layer;
[0057] 4: Third coating layer.
[0058] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0059] To enable those skilled in the art to better understand the present invention, this application will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the invention and are not intended to limit its scope. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. When the following description relates to the accompanying drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements.
[0060] Halide solid electrolytes belong to the key material technology field of all-solid-state lithium batteries and are commonly used in power batteries for new energy vehicles, energy storage batteries, and high-safety electrochemical energy storage devices. These materials generally serve as ion-conducting media in the battery and need to form a stable solid-state electrochemical system together with the positive and negative electrode active materials.
[0061] However, existing halide solid electrolytes have a fatal flaw: they have numerous unsaturated coordination sites on their surface, exhibit extremely high chemical activity, and are highly sensitive to air, water, and oxygen. In normal environments, halide electrolytes undergo rapid hydrolysis side reactions, specifically manifested as: surface Cl... - It reacts with H2O in the air to produce corrosive HCl gas, and at the same time generates lithium salt insulating impurities, causing the electrolyte surface structure to become loose and collapse. Long-term exposure to air will also react with CO2 to produce a lithium carbonate passivation layer, which greatly hinders lithium ion transport and causes the electrolyte conductivity to decrease sharply.
[0062] To address this, the applicant coated the surface of the halide solid electrolyte with metal oxides or metal-like oxides to improve its air, water, and oxygen stability. However, the applicant discovered that while the surface metal oxide or metal-like oxide coating could improve the barrier properties, it also tended to increase interfacial impedance, weakening the high ionic conductivity inherent in the halide electrolyte itself. Therefore, the applicant first formed a fast ion conductor material as a first coating layer on the surface of the halide solid electrolyte, followed by a third coating layer of metal oxide or metal-like oxides. This way, the first coating layer improved the ionic conductivity of the halide solid electrolyte, and the third coating layer improved its air, water, and oxygen stability. However, the applicant subsequently discovered that the first and third coating layers had significant differences in thermal expansion, crystal structure, and electrical properties, with no transition buffer at the interface. This made them highly susceptible to problems such as thermal mismatch, microcracks, interlayer delamination, and interfacial water seepage, resulting in limited stability improvement and poor structural reliability. In response, the applicant provides a second coating layer between the first and third coating layers. The second coating layer includes at least one of lithium-doped composite oxide, lithium-containing phosphate, and lithium-containing silicate. Through the above-mentioned layered coating structure, lithium-ion transport can be taken into account on the side close to the substrate, environmental barrier can be strengthened on the outside, and the interlayer transition relationship can be improved by the intermediate layer, thereby providing a technical basis for the subsequent synergistic improvement of conductivity, protection and structural integrity.
[0063] Figure 1 This is a schematic diagram of the structure of the halide solid electrolyte in some embodiments of this application. For example... Figure 1As shown, in a first aspect, this application provides a halide solid electrolyte, including a substrate 1 and a coating layer, the coating layer including a first coating layer 2, a second coating layer 3 and a third coating layer 4; the first coating layer 2 is coated on the surface of the substrate 1, the second coating layer 3 is coated on the surface of the first coating layer 2, and the third coating layer 4 is coated on the surface of the second coating layer 3.
[0064] The chemical formula of matrix 1 includes Li3MCl6, wherein M includes at least one of Y, Sc, In, Ga and La;
[0065] The first cladding layer 2 includes a fast ion conductor material;
[0066] The second coating layer 3 includes at least one of lithium aluminate, lithium silicate and lithium phosphate;
[0067] The third coating layer 4 includes metal oxides or metal-like oxides.
[0068] In this application, substrate 1 serves as the main ion-conducting phase of the halide solid electrolyte. Its chemical formula, Li3MCl6, represents the halide crystal framework composed of lithium, metal element M, and chlorine. The selection of M affects the cell size, lithium-ion migration barrier, and the material's sensitivity to the external environment. For example, when M is Y, Sc, or In, a higher room-temperature ionic conductivity can be obtained. When Ga or La is introduced alone or in combination with the aforementioned elements, the lattice stability and particle surface chemical state can be further adjusted, thereby achieving better interfacial compatibility between the coating layer and substrate 1.
[0069] The first coating layer 2 is disposed on the surface of the substrate 1 and in direct contact with the substrate 1. Its material is a fast-ion conductor, used to establish an inner interface compatible with lithium-ion migration on the outside of the halide substrate 1. The first coating layer 2 is selected from a fast-ion conductor material that can provide lithium-ion transport and is chemically compatible with the surface of the substrate 1. This layer preferentially covers high-energy sites and defect sites on the surface of the substrate 1, suppressing the direct exposure of active sites or unstable coordination environments on the halide surface, while maintaining the continuity of lithium-ion migration at the interface.
[0070] The second coating layer 3 is coated on the surface of the first coating layer 2, and is used to construct a property transition region between the inner fast ion conductor and the third coating layer 4. The second coating layer 3 includes at least one of lithium aluminate, lithium silicate, and lithium phosphate. The thermal expansion coefficient and ionic conductivity of the material of the second coating layer 3 are between those of the first coating layer 2 and the third coating layer 4. It plays a core role in property transition, stress buffering, and interface bonding enhancement, solving the defects of interlayer cracking and weak bonding between the first coating layer 2 and the third coating layer 4. This layer is different from the ion-conducting interface layer of the first coating layer 2 and the environmental barrier layer of the third coating layer 4. Instead, it establishes a buffer between mechanical properties, lattice compatibility, and interfacial chemical stability. Its function is to reduce the interruption of ion transport with the first coating layer 2 and improve the structural retention ability of the interface, so that after the formation of the third coating layer 4, it is not easy to form interlayer defects due to differences in interlayer properties or particle surface roughness.
[0071] The third coating layer 4 is located on the outermost side and covers the surface of the second coating layer 3. Its material includes metal oxides or metal-like oxides.
[0072] Metal oxides or metal-like oxides have the characteristics of low surface energy, high density and strong chemical inertness, which can effectively block the penetration of external water vapor and oxygen, inhibit the hydrolysis failure of core halides from the source, and greatly improve air stability.
[0073] In summary, the innermost first coating layer 2 directly contacts the halide solid electrolyte substrate 1 through a fast ion conductor material, covering surface defects and active sites without significantly disrupting lithium-ion migration pathways. This process achieves simultaneous interface passivation and ion transport. The middle second coating layer 3 forms a transition layer with both structural support and ion compatibility through lithium-doped composite oxides, lithium-containing phosphates, or lithium-containing silicates. This layer buffers the differences in physical properties and chemical environment between the first coating layer 2 and the third coating layer 4, reducing stress concentration and interlayer discontinuities at the multilayer interface. The outermost third coating layer 4 establishes the first barrier against the environmental medium through metal oxides or metal-like oxides, inhibiting the inward diffusion of moisture and oxygen. Through this layering principle, the three layers are not simply superimposed, but maintain lithium conductivity continuity near the substrate 1, strengthen barrier properties near the environment, and achieve interlayer compatibility in the middle. This results in a gradient change in structure and a progressive synergy in function across the multilayer coating.
[0074] In one specific embodiment, the fast ion conductor material includes LiNbO3, LiTaO3, Li4SiO4, Li3PS4, and Li7P3S. 11 At least one of Li3PO4.
[0075] In this application, the first coating layer 2 may be composed of LiNbO3, LiTaO3, Li4SiO4, Li3PS4, or Li7P3S. 11 LiNbO3 and LiTaO3, either alone or in combination with two or more of them, can form a continuous, fast-migrating lithium-ion channel on the surface of substrate 1. Since LiNbO3 and LiTaO3 are lithium-ion conductors with good structural stability, their coating can passivate active sites on the surface of substrate 1 while reducing interfacial side reactions. Li4SiO4 and Li3PO4 can provide relatively stable ion migration pathways through silicon-oxygen or phosphorus-oxygen frameworks and improve the compatibility of the coating layer with the halide substrate 1. Li3PS4 and Li7P3S... 11 As a sulfide fast ion conductor, it has a high intrinsic lithium-ion conductivity, which enables it to maintain continuous ion transport at a low interfacial impedance.
[0076] In one specific embodiment, the lithium aluminate includes at least one of LiAlO2 and LiAl5O8.
[0077] Lithium aluminates possess extremely low raw material costs and excellent chemical structural stability. The aluminum-oxygen polyhedra can construct a dense and stable inorganic framework with a regular lattice structure and few defects, making them less prone to structural distortion and side reactions in solid-state battery systems. Furthermore, lithium aluminates exhibit mild physicochemical properties and excellent interfacial compatibility, effectively optimizing the overall structural stability of the coating layer.
[0078] In one specific embodiment, the lithium silicate includes at least one of Li2SiO3 and Li2Si2O5.
[0079] The chain / layered structure of lithium silicates has higher fracture toughness and deformation coordination ability, and the dense silicon-oxygen network in lithium silicates can block the penetration of small molecules. The melting and softening temperature is moderate, and low-temperature annealing can achieve dense interlayer sintering, which greatly reduces the porosity defects of the coating layer.
[0080] In one specific embodiment, the lithium phosphate includes at least one of LiZr2(PO4)3, LiTi2(PO4)3 and LiHf2(PO4)3.
[0081] Lithium phosphate has a NASICON-type structure. The rigid PO skeleton provides extremely high chemical and thermal stability. It is resistant to water vapor and acid corrosion, and has certain ion conductivity. Therefore, it can effectively connect the first coating layer 2 and the third coating layer 4.
[0082] The physical properties (including coefficient of thermal expansion, lattice structure, and ion conductivity) of the second coating layer 3 in this application are between those of the first coating layer 2 and the third coating layer 4. This balances the differences in physical properties between the first coating layer 2 and the third coating layer 4, and plays a crucial role in transition, stress buffering, and enhancing interfacial bonding between them. Furthermore, the lattice structure of the second coating layer 3 allows for lithium ion migration, maintaining the overall ion pathway. Lithium aluminate, lithium silicate, and lithium phosphate can intercept permeated water vapor, achieving a gradient transition from the inside to the outside and resolving the defects of interlayer cracking and weak bonding between the first coating layer 2 and the third coating layer 4.
[0083] In one specific embodiment, the metal oxide includes at least one of Al2O3, TiO2, ZrO2 and HfO2; the metal-like oxide includes SiO2.
[0084] The third coating layer 4 utilizes the inorganic dense structure of the metal oxide itself to form a continuous and stable barrier interface on the particle surface. Combined with its low surface adsorption activity, this weakens the channels for water and oxygen molecules to diffuse inward. Specifically, Al₂O₃ can form a dense oxide barrier, TiO₂ can provide barrier capabilities while maintaining good surface stability, ZrO₂ and HfO₂ have high chemical inertness and structural density, and SiO₂ can inhibit water vapor permeation through a stable silicon-oxygen network. By limiting the metal oxide or metal-like oxide to the above material system, the third coating layer 4 can maintain low surface reactivity in air or trace water and oxygen environments, and reduce the risk of moisture decomposition of the halide matrix 1.
[0085] In one specific embodiment, the thickness of the coating layer is less than or equal to 200 nm.
[0086] The coating layer is a three-layer gradient coating structure disposed on the outer surface of the halide solid electrolyte substrate 1, and its overall thickness is controlled to be no more than 200 nm to ensure that a continuous protective film is formed without excessively occupying the ion transport space. The coating layer thickness here refers to the total thickness of the first coating layer 2, the second coating layer 3, and the third coating layer 4 along the radial direction of the substrate 1. The nanoscale thin-layer design allows the coating layer to cover particle surface defects without significantly increasing the lithium ion passage path due to excessive layer thickness.
[0087] By controlling the total thickness of the three-layer coating to no more than 200 nm, the functions of each layer can be synergistically utilized at an extremely thin scale. This avoids the accumulation of interfacial impedance caused by the superposition of multiple layers and reduces the risk of microcracks and local detachment, thereby improving the stability of halide solid electrolytes during air exposure, transportation and cell assembly, while maintaining high ionic conductivity and structural integrity.
[0088] In one specific embodiment, the coating layer accounts for 2-12% of the mass of the halide solid electrolyte.
[0089] In this application, the mass percentage of the coating layer is controlled at 2-12%. This ensures that, while the coating material is sufficient to form a continuous protective film, excessive coating can prevent a decrease in the proportion of the electrolyte, a significant elongation of the ion transport path, and an increase in interfacial impedance. A lower mass percentage results in a thinner and lighter coating layer, which helps maintain the high ionic conductivity of the main electrolyte. A higher mass percentage provides more comprehensive coverage, enhancing the shielding effect against water, oxygen, and external impurities, thereby improving environmental adaptability. By limiting the mass percentage to the balanced range of 2-12%, the first coating layer 2, the second coating layer 3, and the third coating layer 4 can function synergistically: the inner layer ensures ion conduction, the middle layer improves transition, and the outer layer strengthens protection. This ensures that the halide solid electrolyte exhibits good air stability while maintaining low interfacial impedance and high effective ionic conductivity during transport, compounding, and assembly.
[0090] In one specific embodiment, the thickness of the first coating layer 2 is 10-60 nm.
[0091] By controlling the thickness of the first coating layer 2 within the above-mentioned range, the continuity of ion transport can be ensured while avoiding excessive coating thickness that would increase the interface impedance.
[0092] In one specific embodiment, the thickness of the second coating layer 3 is 10-50 nm.
[0093] By controlling the thickness of the second covering layer 3 within the above-mentioned range, interlayer bonding can be enhanced and thermal stress and structural mismatch can be alleviated.
[0094] In one specific embodiment, the thickness of the third coating layer 4 is 10-100 nm.
[0095] By controlling the thickness of the third coating layer 4 within the above range, water and oxygen intrusion can be effectively suppressed and surface side reactions reduced.
[0096] In one specific embodiment, the room temperature ionic conductivity retention rate of the halide solid electrolyte is greater than or equal to 93% after being exposed to ambient air at a dew point of -45°C for 4 hours.
[0097] The halide solid electrolyte retains 93% or more of its room temperature ionic conductivity after 4 hours of exposure to ambient air at a dew point of -45°C. This indicates that the coating layer does not significantly block lithium-ion migration channels, and that the material maintains near-intrinsic conductivity during air, water-oxygen contact, and assembly and transport processes.
[0098] In one specific embodiment, the method for preparing a halide solid electrolyte includes:
[0099] S1: Under an inert protective atmosphere, the matrix 1 is dispersed in the first coating liquid, and a first stirring reaction is carried out at 40-65°C, followed by drying and first annealing to obtain the first intermediate; wherein the first coating liquid includes a fast ion conductor material;
[0100] S2: Under an inert protective atmosphere, the first intermediate is dispersed in the second coating solution, and a second stirring reaction is carried out at 40-65°C, followed by drying and a second annealing to obtain the second intermediate; wherein the second coating solution includes at least one of lithium aluminate, lithium silicate and lithium phosphate;
[0101] S3: Under an inert protective atmosphere, the second intermediate is dispersed in the third coating solution, and a third stirring reaction is carried out at 40-65℃. After drying and third annealing, a halide solid electrolyte is obtained. The third coating solution includes metal oxides or metal-like oxides. The mass percentage of water in the first, second, and third coating solutions is independently less than 10 ppm.
[0102] The temperature of the first annealing is higher than the temperature of the second annealing, and the temperature of the second annealing is higher than the temperature of the third annealing.
[0103] Secondly, this application provides a method for preparing the above-mentioned halide solid electrolyte, comprising:
[0104] S1: Under an inert protective atmosphere, the matrix 1 is dispersed in the first coating liquid, and a first stirring reaction is carried out at 40-65°C, followed by drying and first annealing to obtain the first intermediate; wherein the first coating liquid includes a fast ion conductor material;
[0105] S2: Under an inert protective atmosphere, the first intermediate is dispersed in the second coating solution, and a second stirring reaction is carried out at 40-65°C, followed by drying and a second annealing to obtain the second intermediate; wherein the second coating solution includes at least one of lithium aluminate, lithium silicate and lithium phosphate;
[0106] S3: Under an inert protective atmosphere, the second intermediate is dispersed in the third coating solution, and a third stirring reaction is carried out at 40-65℃. After drying and third annealing, a halide solid electrolyte is obtained. The third coating solution includes metal oxides or metal-like oxides. The mass percentage of water in the first, second, and third coating solutions is independently less than 10 ppm.
[0107] The temperature of the first annealing is higher than the temperature of the second annealing, and the temperature of the second annealing is higher than the temperature of the third annealing.
[0108] In this application, the matrix 1 is first dispersed in a first coating liquid containing fast ion conductor material and stirred in the range of 40-65°C, so that the fast ion conductor material is preferentially adsorbed on the surface of the matrix 1 particles and forms an initial reaction layer. Then, after drying and first annealing, a first intermediate with a first coating layer 2 coated on the surface of the matrix 1 is obtained.
[0109] The first intermediate is then dispersed in a second coating solution containing lithium-doped composite oxide, lithium phosphate, or lithium silicate for a second stirring reaction, drying, and annealing. This allows the coating material in the second coating solution to cover the outside of the first coating layer 2 and fill interlayer defects, forming a second intermediate on the surface of the substrate 1, which is sequentially coated with the first coating layer 2 and the second coating layer 3. The temperature of 40-65℃ helps to maintain particle dispersion and coating uniformity, and avoids local agglomeration that causes discontinuous coating.
[0110] Finally, the second intermediate is dispersed in a third coating solution containing metal oxides or metal-like oxides, followed by a third stirring reaction, drying, and annealing. This forms a dense hydrophobic barrier on the outer layer, blocking contact between external water and oxygen and suppressing surface side reactions, thereby maintaining the room-temperature ionic conductivity of the halide solid electrolyte. Through three sequential coatings, the halide solid electrolyte of this application is formed, wherein the first coating layer 2 is responsible for lithium-ion transport, the second coating layer 3 is responsible for interface transition, and the third coating layer 4 is responsible for environmental barrier, thus achieving a synergistic balance between conductivity and structural stability.
[0111] This application employs a liquid-phase adsorption and annealing preparation process. The materials of each coating layer are uniformly adsorbed as a monolayer on the surface of the substrate 1 and crystallized at low temperature, avoiding the problems of thermal decomposition and lattice destruction of the halide substrate 1 caused by high-temperature processes. Compared with dry coating, the coating layer is continuous and dense, without exposed defects, and has extremely low porosity. Furthermore, by limiting the temperatures of the first, second, and third annealing, the influence of the second annealing on the first coating layer 2 formed by the first annealing can be minimized, and the influence of the third annealing on the second coating layer 3 formed by the second annealing can be minimized.
[0112] In one embodiment, the inert atmosphere includes at least one of argon, nitrogen, and helium.
[0113] In one specific embodiment, the oxygen content is less than 0.1 ppm and the water content is less than 0.01 ppm in an inert atmosphere. The preparation is carried out under an inert protective atmosphere, which can isolate water vapor and oxygen and prevent the solid electrolyte from hydrolyzing and deteriorating.
[0114] In one specific embodiment, in S1, the temperature is increased to 100-400°C at a heating rate of 1-5°C / min for a first annealing process of 1-5 hours.
[0115] The first annealing corresponds to the curing and interface stabilization treatment of the first coating layer 2; the annealing temperature is controlled between 100-400℃, which allows the coating material in the first coating liquid to decompose, condense, or crystallize and form a continuous coating layer without causing significant thermal damage to the crystal lattice of the substrate 1. The above-mentioned annealing temperature and time allow the first coating layer 2 to be fully densified and to complete its bonding with the surface of the substrate 1.
[0116] In one specific embodiment, in S2, the temperature is increased to 100-400°C at a heating rate of 1-5°C / min for a second annealing process of 1-5 hours.
[0117] The second annealing corresponds to the curing and interface stabilization treatment of the second coating layer 3. The annealing temperature is controlled between 100-400℃, which allows the coating material in the second coating liquid to decompose, condense, or crystallize, forming a continuous coating layer without causing significant thermal damage to the crystal lattice of the substrate 1 and the first coating layer 2. The aforementioned annealing temperature and time allow the second coating layer 3 to be fully densified and to complete its bonding with the surface of the first coating layer 2.
[0118] In one specific embodiment, in S3, the temperature is increased to 100-400°C at a heating rate of 1-5°C / min for a third annealing process of 1-5 hours.
[0119] The third annealing corresponds to the curing and interface stabilization treatment of the third coating layer 4; the annealing temperature is controlled between 100-400℃, which allows the coating material in the third coating liquid to decompose, condense, or crystallize and form a continuous coating layer without causing significant thermal damage to the crystal lattice of the second coating layer 3. The above-mentioned annealing temperature and time allow the third coating layer 4 to be fully densified and to complete its bonding with the surface of the second coating layer 3.
[0120] In one specific embodiment, when the temperature difference between the first annealing and the third annealing is less than or equal to 60°C, the difference in the thermal history experienced by the three coating layers can be reduced, the residual thermal stress caused by thermal shrinkage mismatch during the cooling process can be reduced, and the appearance of microcracks, pores or peeling off between coating layers at the interface between two adjacent coating layers can be effectively avoided, ensuring that a close contact and low impedance interface is formed between two adjacent coating layers, providing a continuous and stable cross-layer transport channel for lithium ions.
[0121] In one specific embodiment, the first stirring reaction takes 2-5 hours.
[0122] By limiting the first stirring reaction time to 2-5 hours, a balance can be achieved between material mass transfer, interface wetting, and stable particle dispersion.
[0123] In one specific embodiment, the second stirring reaction takes 2-5 hours.
[0124] By limiting the second stirring reaction time to 2-5 hours, a balance can be achieved between material mass transfer, interface wetting, and stable particle dispersion.
[0125] In one specific embodiment, the third stirring reaction takes 2-5 hours.
[0126] By limiting the third stirring reaction time to 2-5 hours, a balance can be achieved between material mass transfer, interface wetting, and stable particle dispersion.
[0127] In one specific embodiment, the first coating liquid further includes a dispersant and an organic solvent.
[0128] In one specific embodiment, the second coating liquid further includes a dispersant and an organic solvent;
[0129] In one specific embodiment, the third coating liquid also includes a dispersant and an organic solvent.
[0130] Each of the first, second, and third coating solutions may further include a dispersant and an organic solvent. The dispersant is used to reduce the tendency of the coating material particles in the corresponding coating solution to form a stable dispersion system in the coating solution for fast ion conductor materials, lithium aluminates, lithium silicates, lithium phosphates, or metal oxides or metal-like oxides. The organic solvent is used as a liquid medium to carry the coating components and improve the flowability, so that the matrix 1 and the material to be coated can fully contact under the first, second, and third stirring reaction conditions at 40-65℃.
[0131] In one specific embodiment, the dispersant in the first coating liquid, the second coating liquid, and the third coating liquid each independently includes at least one of polyvinylpyrrolidone (PVP), ethylene glycol, and polyethylene glycol.
[0132] In one specific embodiment, the mass percentage of the dispersant in the first coating liquid, the second coating liquid, and the third coating liquid is independently 0.1% to 3%.
[0133] In one specific embodiment, the organic solvents in the first coating liquid, the second coating liquid, and the third coating liquid each independently include at least one of anhydrous ethanol, anhydrous isopropanol, anhydrous acetonitrile, and anhydrous tetrahydrofuran.
[0134] In one specific embodiment, the stirring speed of the first stirring reaction is 300-650 r / min.
[0135] In one specific embodiment, the stirring speed of the second stirring reaction is 300-650 r / min.
[0136] In one specific embodiment, the stirring speed of the third stirring reaction is 300-650 r / min.
[0137] In one specific embodiment, the vacuum degree of drying is less than or equal to -0.08 MPa.
[0138] Thirdly, this application provides a solid-state battery, which includes the aforementioned halide solid electrolyte.
[0139] This solid-state battery uses a halide solid electrolyte as the ion conduction medium, enabling it to form a stable all-solid-state electrochemical system together with the positive and negative electrode active materials. Since the halide solid electrolyte uses Li3MCl6 material as the substrate 1, and its surface is sequentially coated with a first coating layer 2, a second coating layer 3, and a third coating layer 4, the first coating layer 2 helps maintain lithium-ion migration channels, the second coating layer 3 improves interlayer transition and interface matching, and the third coating layer 4 enhances the barrier against water and oxygen. This balances air stability and ion conductivity, allowing the electrolyte to maintain good structural integrity and interface stability during transport, recombination, and assembly. This reduces the internal interface impedance of the battery and improves cycle stability, making it more suitable for applications in power batteries, energy storage batteries, and high-safety energy storage devices.
[0140] In one specific embodiment, the solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the solid electrolyte layer includes a halide solid electrolyte.
[0141] In one specific embodiment, the solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode includes a halide solid electrolyte.
[0142] The technical solution of this application and how the technical solution of this application solves the above-mentioned technical problems are described in detail below with specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments. The embodiments of this application will now be described with reference to the accompanying drawings.
[0143] Example 1
[0144] The preparation method of the halide solid electrolyte in this embodiment includes the following steps:
[0145] (1) First coating layer
[0146] Matrix pretreatment: In a glove box, 10g of high-purity Li3ScCl6 halide electrolyte powder was ground and passed through a 300-mesh sieve to remove large agglomerated particles, resulting in a Li3ScCl6 matrix with uniform particle size.
[0147] Preparation of the first coating solution: Take 0.2 g of nano-sized LiTaO3 powder, disperse it in anhydrous ethanol, add 1% PVP, stir at 50℃ for 40 min to obtain a uniformly dispersed first coating solution containing 2% LiTaO3.
[0148] The Li3ScCl6 electrolyte powder was dispersed in the first coating solution and stirred magnetically at 450 r / min for 3 h at a constant temperature of 50℃ to obtain the first mixed slurry.
[0149] After centrifuging the first mixed slurry, it was dried at 80°C under vacuum for 10 hours (vacuum degree of -0.09MPa) to remove organic solvents; then the temperature was raised to the first annealing temperature of 250°C at a heating rate of 2°C / min, held at that temperature for 2 hours, and then naturally cooled to room temperature to obtain the first intermediate.
[0150] (2) Second coating layer
[0151] Preparation of the second coating solution: Take 0.2g LiZr2(PO4)3, disperse it in anhydrous ethanol, add 1% PVP, stir at 50℃ for 40min to obtain a uniformly dispersed second coating solution containing 2% LiZr2(PO4)3.
[0152] The first intermediate was dispersed in the second coating liquid, and the mixture was kept at a constant temperature of 50°C and magnetically stirred at 450 r / min for 3 hours to obtain the second mixed slurry.
[0153] After centrifugation, the second mixed slurry was dried at 80°C under vacuum for 10 hours (vacuum degree of -0.09MPa) to remove organic solvents; then it was annealed at 230°C for 2 hours at a heating rate of 2°C / min to obtain the second intermediate.
[0154] (3) Third coating layer
[0155] Preparation of the third coating solution: Take 0.2g ZrO2, disperse it in anhydrous ethanol, add 1% PVP, stir at 50℃ for 40min to obtain a uniformly dispersed third coating solution containing 2% ZrO2.
[0156] The second intermediate was dispersed in the third coating liquid, and the mixture was kept at a constant temperature of 50°C and magnetically stirred at 450 r / min for 3 hours to obtain the third mixed slurry.
[0157] The third mixed slurry was centrifuged and then dried under vacuum at 80°C for 10 hours (vacuum degree: -0.09MPa) to remove organic solvents. Subsequently, it was annealed at 200°C for 3 hours at a heating rate of 2°C / min to obtain a halide solid electrolyte N1 with a coating layer comprising 6% by mass. Its structural schematic diagram is shown below. Figure 1 As shown.
[0158] Example 2
[0159] The preparation method of the halide solid electrolyte in this embodiment is basically the same as that in Example 1, except that:
[0160] In step (1), a first coating solution containing 3% LiNbO3 is prepared using 0.3g of LiNbO3 powder.
[0161] In step (2), a second coating solution containing 2% LiAlO2 is prepared using 0.2g LiAlO2.
[0162] In step (3), 0.3g Al2O3 is used to prepare a third coating solution containing 3% Al2O3, and finally a halide solid electrolyte N2 with a coating layer mass ratio of 8% is obtained.
[0163] Example 3
[0164] The preparation method of the halide solid electrolyte in this embodiment is basically the same as that in Example 1, except that:
[0165] In step (1), Li3InCl6 is used as the matrix, and 0.2g of LiTaO3 powder is used to prepare a first coating solution containing 2% LiTaO3.
[0166] In step (2), a second coating solution containing 1% LiTi2(PO4)3 is prepared using 0.1g LiTi2(PO4)3.
[0167] In step (3), 0.2g TiO2 is used to prepare a third coating solution containing 2% TiO2, and finally a halide solid electrolyte N3 with a coating layer mass ratio of 5% is obtained.
[0168] Example 4
[0169] The preparation method of the halide solid electrolyte in this embodiment is basically the same as that in Example 1, except that:
[0170] In step (1), Li3InCl6 is used as the matrix, and 0.3g of Li3PO4 powder is used to prepare a first coating solution containing 3% Li3PO4.
[0171] In step (2), a second coating solution containing 3% Li2SiO3 is prepared using 0.3g Li2SiO3.
[0172] In step (3), 0.4g SiO2 is used to prepare a third coating solution containing 4% SiO2, and finally a halide solid electrolyte N4 with a coating layer mass ratio of 10% is obtained.
[0173] Example 5
[0174] The preparation method of the halide solid electrolyte in this embodiment is basically the same as that in Example 1, except that:
[0175] In step (1), Li3YCl6 is used as the matrix, and 0.25g of Li4SiO4 powder is used to prepare a first coating solution containing 2.5% Li4SiO4.
[0176] In step (2), a second coating solution containing 1.5% LiHf2(PO4)3 is prepared using 0.15g LiHf2(PO4)3.
[0177] In step (3), 0.3g HfO2 is used to prepare a third coating solution containing 3% HfO2, and finally a halide solid electrolyte N5 with a coating layer mass ratio of 7% is obtained.
[0178] Example 6
[0179] The preparation method of the halide solid electrolyte in this embodiment is basically the same as that in Example 1, except that:
[0180] In step (1), Li3YCl6 was used as the matrix, 0.3g of Li3PS4 powder was dispersed in anhydrous acetonitrile, 1% PVP was added, and a first coating solution containing 3% Li3PS4 was prepared.
[0181] In step (2), a second coating solution containing 3% LiAl5O8 is prepared using 0.3g LiAl5O8.
[0182] In step (3), 0.3g Al2O3 is used to prepare a third coating solution containing 3% Al2O3, and finally a halide solid electrolyte N6 with a coating layer mass ratio of 9% is obtained.
[0183] Example 7
[0184] The preparation method of the halide solid electrolyte in this embodiment is basically the same as that in Example 1, except that:
[0185] In step (1), a first coating solution containing 4% LiNbO3 and LiTaO3 is prepared using 0.4g of LiNbO3:LiTaO3=1:1 powder.
[0186] In step (2), a second coating solution containing 3% LiZr2(PO4)3 is prepared using 0.3g LiZr2(PO4)3.
[0187] In step (3), 0.4g ZrO2 is used to prepare a third coating solution containing 4% ZrO2, and finally a halide solid electrolyte N7 with a coating layer mass ratio of 11% is obtained.
[0188] Comparative Example 1
[0189] The halide electrolyte NS1 in this comparative example was Li3ScCl6, which was used for testing.
[0190] Comparative Example 2
[0191] The preparation method of the halide solid electrolyte in this comparative example is basically the same as that in Example 1, except that step (2) is not included.
[0192] In step (1), a first coating solution containing 2% LiNbO3 is prepared using 0.2g of LiNbO3 powder.
[0193] In step (3), 0.2g Al2O3 is used to prepare a third coating solution containing 2% Al2O3, and finally a halide solid electrolyte NS2 with a coating layer mass ratio of 4% is obtained.
[0194] Comparative Example 3
[0195] The preparation method of the halide solid electrolyte in this comparative example specifically includes:
[0196] In a glove box, 0.2g each of LiTaO3, LiZr2(PO4)3, and ZrO2 were directly placed into a mortar and ground. The three materials were pre-mixed evenly to obtain a mixed powder. The mixed powder was dispersed in anhydrous ethanol, 1% PVP was added, and the mixture was stirred at 50℃ for 40 min to obtain a uniformly dispersed suspension. 10g of Li3ScCl6 electrolyte powder was added for coating. The reaction temperature was kept constant at 50℃ and magnetically stirred at 450 r / min for 3 h to obtain a mixed slurry. The mixed slurry was centrifuged and then vacuum dried at 80℃ for 10 h. Subsequently, the temperature was increased to 250℃ at a rate of 2℃ / min and held for 3 h. The mixture was then naturally cooled to room temperature to obtain a halide solid electrolyte NS3 with a coating layer mass ratio of 6%. The components of the coating layer in NS3 were mixed and distributed.
[0197] Test method:
[0198] 1) Ionic Conductivity Test: 100 mg of the halide solid electrolyte from the examples and comparative examples were weighed and placed inside a pressure molding mold. A pressure of 300 MPa was applied to the halide solid electrolyte for pressure molding. Under pressure, the impedance value of the halide solid electrolyte was measured at room temperature (25°C) using an electrochemical workstation (Solarton 1260) and electrochemical impedance spectroscopy. The real value of the impedance at the measurement point with the smallest absolute value of the phase of multiple impedances was taken as the resistance value (RSE) of the electrolyte material relative to ion conduction. Using this resistance value, the room temperature ionic conductivity was calculated based on the formula σ0 = (RSE × S / t)⁻¹. Where σ0 is the ionic conductivity, RSE is the measured resistance value of the halide solid electrolyte, S is the surface area of the pressure-applied halide solid electrolyte, and t is the thickness of the pressure-applied halide solid electrolyte.
[0199] 2) Air stability test: After the ionic conductivity test as shown above is performed, the room temperature ionic conductivity of the sample is recorded as σ0. Take 2g of sample and place it in a -45℃ dew point environment for 4 hours. Measure the room temperature ionic conductivity after placement. The test method is the same as above. The ionic conductivity after exposure is σ1.
[0200] 3) Ionic conductivity retention rate: Based on the above test results of σ0 and σ1, the ionic conductivity retention rate is calculated using the formula: σ1 / σ0×100%.
[0201] 4) Preparation and testing of mold batteries
[0202] After the halide solid electrolytes of the examples and comparative examples were respectively fabricated as positive electrode sheets, they were assembled with lithium indium alloy sheets and electrolyte layers according to the following method to obtain a mold battery. The method includes:
[0203] NCM811 cathode material, halide solid electrolyte, conductive agent (VGCF) and binder (PTFE) were uniformly mixed in a mass ratio of 70:26.5:3:0.5 to prepare a cathode sheet, which was then stamped into a disc with a diameter of 10 mm. Subsequently, a Li6PS5Cl sulfide solid electrolyte was used as the electrolyte layer, and a lithium indium alloy was used as the anode. Together with stainless steel current collectors on both sides, they were assembled into a mold battery that could be used for testing.
[0204] First-cycle discharge specific capacity: The assembled mold battery was placed in a 25℃ environment and left to stand for 12 hours; a constant current charge-discharge test was performed using a battery tester. First, it was charged at a constant current of 1C to the charging cutoff voltage, and then discharged at a constant current of 1C to the discharging cutoff voltage. The first-cycle discharge specific capacity was recorded.
[0205] Capacity retention after 300 cycles: At 25°C, the capacitor was charged at a constant current rate of 1C to 4.30V, then charged at a constant voltage rate of 0.05C to 4.30V, and then discharged at a discharge rate of 1C to 2.7V. This charge-discharge cycle was repeated 300 times. The discharge capacity Q1 at the first cycle and the discharge capacity Q at the 300th cycle were measured. 300 300-cycle capacity retention rate Q=Q 300 / Q1×100%.
[0206] Table 1
[0207]
[0208] As can be seen from the examples and comparative examples in Table 1, after coating modification of Li3ScCl6, Li3InCl6, and Li3YCl6 respectively, compared with the comparative examples, the examples of this application showed that the ionic conductivity retention rate was all above 93% after being placed in a -45℃ dew point environment for 4 hours, and the long-term cycle stability of the battery was also significantly optimized. Among them, Comparative Example 1, which was not coated, had poor air stability and significant capacity decay during cycling; Comparative Example 2, which was coated with only two layers, and Comparative Example 3, which was directly coated with a mixture of three layers, had a certain improvement effect on the ionic conductivity retention rate and long-term cycle stability of the halide solid electrolyte, but the improvement was limited compared with the examples of this application.
[0209] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A halide solid electrolyte, characterized in that, It includes a substrate and a coating layer, the coating layer including a first coating layer, a second coating layer and a third coating layer; the first coating layer covers at least a portion of the surface of the substrate, the second coating layer covers at least a portion of the surface of the first coating layer, and the third coating layer covers at least a portion of the surface of the second coating layer; The chemical formula of the matrix includes Li3MCl6, wherein M includes at least one of Y, Sc, In, Ga and La; The first coating layer comprises a fast ion conductor material; The second coating layer includes at least one of lithium aluminate, lithium silicate, and lithium phosphate; The third coating layer comprises metal oxides and / or metal-like oxides.
2. The halide solid electrolyte according to claim 1, characterized in that, The fast ion conductor materials include LiNbO3, LiTaO3, Li4SiO4, Li3PS4, and Li7P3S. 11 At least one of Li3PO4.
3. The halide solid electrolyte according to claim 1, characterized in that, The lithium aluminate includes at least one of LiAlO2 and LiAl5O8; And / or, lithium silicates include at least one of Li2SiO3 and Li2Si2O5; And / or, lithium phosphate includes at least one of LiZr2(PO4)3, LiTi2(PO4)3 and LiHf2(PO4)3.
4. The halide solid electrolyte according to claim 1, characterized in that, The metal oxide includes at least one of Al2O3, TiO2, ZrO2, and HfO2; And / or, the metal-like oxide includes SiO2.
5. The halide solid electrolyte according to claim 1, characterized in that, The thickness of the coating layer is less than or equal to 200 nm.
6. The halide solid electrolyte according to claim 1 or 5, characterized in that, In the halide solid electrolyte, the coating layer accounts for 2-12% of the total mass.
7. The halide solid electrolyte according to claim 1 or 5, characterized in that, The thickness of the first coating layer is 10-60 nm; And / or; the thickness of the second coating layer is 10-50 nm; And / or; the thickness of the third coating layer is 10-100 nm.
8. The halide solid electrolyte according to claim 1, characterized in that, The halide solid electrolyte retains a room temperature ionic conductivity of 93% or greater after being exposed to ambient air at a dew point of -45°C for 4 hours.
9. A method for preparing a halide solid electrolyte according to any one of claims 1-8, characterized in that, include: S1: Under an inert protective atmosphere, the matrix is dispersed in a first coating liquid, and a first stirring reaction is carried out at 40-65°C, followed by drying and a first annealing to obtain a first intermediate; The first coating liquid includes the fast ion conductor material; S2: Under an inert protective atmosphere, the first intermediate is dispersed in the second coating liquid, and a second stirring reaction is carried out at 40-65℃. After drying and second annealing, the second intermediate is obtained. The second coating solution includes at least one of lithium aluminate, lithium silicate and lithium phosphate; S3: Under an inert protective atmosphere, the second intermediate is dispersed in the third coating liquid, and a third stirring reaction is carried out at 40-65°C. After drying and third annealing, the halide solid electrolyte is obtained. The third coating solution includes a metal oxide or a metal-like oxide; the water content in the first, second, and third coating solutions is independently less than 10 ppm. The temperature of the first annealing is greater than the temperature of the second annealing, and the temperature of the second annealing is greater than the temperature of the third annealing.
10. The preparation method according to claim 9, characterized in that, In step S1, the temperature is increased to 100-400℃ at a heating rate of 1-5℃ / min to perform the first annealing for 1-5 hours. And / or, in S2, the temperature is increased to 100-400°C at a heating rate of 1-5°C / min for the second annealing for 1-5 hours; And / or, in S3, the temperature is increased to 100-400℃ at a heating rate of 1-5℃ / min to carry out the third annealing for 1-5 hours; And / or, the difference between the temperature of the first annealing and the temperature of the third annealing is less than or equal to 60°C.
11. The preparation method according to claim 9, characterized in that, The first stirring reaction takes 2-5 hours; And / or, the second stirring reaction time is 2-5 hours; And / or, the third stirring reaction time is 2-5 hours.
12. The preparation method according to claim 9, characterized in that, The first coating liquid also includes a dispersant and an organic solvent; And / or, the second coating liquid further includes a dispersant and an organic solvent; And / or, the third coating liquid also includes a dispersant and an organic solvent.
13. The preparation method according to claim 9, characterized in that, The stirring speed for the first stirring reaction is 300-650 r / min; And / or, the stirring speed of the second stirring reaction is 300-650 r / min; And / or, the stirring speed of the third stirring reaction is 300-650 r / min; And / or, the vacuum degree of the drying process is less than or equal to -0.08 MPa.
14. A solid-state battery, characterized in that, The solid-state battery includes the halide solid electrolyte as described in any one of claims 1-8.
15. The solid-state battery according to claim 14, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the solid electrolyte layer includes the halide solid electrolyte.
16. The solid-state battery according to claim 14, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode includes the halide solid electrolyte.
